Fluid retention after shoulder arthroscopy: Gravity flow vs. automated pump-a prospective randomized study - Çatal, Bilgehan; Azboy, İbrahim (Mosby-Elsevier, 2019)
Background: Soft tissue fluid retention due to irrigation is relatively common after shoulder arthroscopy. The objective of this study was to compare fluid retention of 2 irrigation systems of shoulder arthroscopy: gravity flow irrigation and automated pump. Methods: Patients undergoing shoulder arthroscopy were enrolled prospectively and randomized into 2 groups using gravity flow system (GFS) or automated pump system (APS) for irrigation. Net weight gain was the primary outcome measurement to determine periarticular fluid retention. Change in deltoid diameter and postoperative pain were also compared. Results: Forty-two patients were included in the study. There were no statistically significant differences between the GFS and APS groups regarding demographics, surgical procedures, duration of surgery. or the amount of irrigation fluid used. The APS group had greater weight gain per hour (1.46 +/- 0.36 kg/ h vs. 1.1 +/- 0.38 kg/h) than the GFS group. A strong correlation was found between the amount of fluid used and the weight gain in both the GFS and APS groups. But a strong correlation between duration of surgery and weight gain was found in the APS group only. The APS group also had a greater mean deltoid diameter increase (3.33 +/- 1.56 cm vs. 2.1 +/- 1.44 cm) and a higher postoperative first-hour visual analog pain scale score (5.81 +/- 1.2 vs. 3.62 +/- 1.6). Conclusion: APS causes more fluid retention than GFS in shoulder arthroscopy when used for equal duration in similar procedures. Use of APS, prolongation of surgery. and increased amounts of irrigation fluid increase weight gain as a result of fluid retention.
Keywords: Arthroscopy; Automated Pump; Fluid Retention; Gravity Flow; Shoulder; Weight Gain